2003
DOI: 10.1080/03008200390181852
|View full text |Cite
|
Sign up to set email alerts
|

A New Paradigm for Biomineral Formation: Mineralization via an Amorphous Liquid-Phase Precursor

Abstract: Biologically mineralized tissues are well recognized for their unusual crystal morphologies and hierarchically organized composite structures. The soluble acidic macromolecules associated with biominerals are thought to play an important role in modulating the mineral morphology. Our in vitro studies, which use acidic polypeptide additives to modify crystal growth of calcium-based minerals, have demonstrated a crystallization mechanism that proceeds via a liquid-phase mineral precursor. Various features of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(98 citation statements)
references
References 35 publications
2
85
0
2
Order By: Relevance
“…Phosphorylated and sulfated glycoproteins [48][49][50] play an important role in the initial stage of biomineralization. It has been suggested that they would take part in the formation of biominerals through amorphous liquid-phase precursors [51]. Ions are the reactants during the biomineralization process and ion minerals are the products.…”
Section: Concerning Protein Chain Synthesis On Apatite and Carbonate-mentioning
confidence: 99%
“…Phosphorylated and sulfated glycoproteins [48][49][50] play an important role in the initial stage of biomineralization. It has been suggested that they would take part in the formation of biominerals through amorphous liquid-phase precursors [51]. Ions are the reactants during the biomineralization process and ion minerals are the products.…”
Section: Concerning Protein Chain Synthesis On Apatite and Carbonate-mentioning
confidence: 99%
“…According to this approach, a PAA with a low MW is used to imitate the stabilizing function of dentin matrix protein 1 (DMP1) on amorphous calcium phosphate precursors (He et al, 2005;Mai et al, 2009;Zhong et al, 2015). The interaction of the Portland cement with SBF reduces these precursors to a nanoscale (Olszta et al, 2003;Mai et al, 2009) and thus prevents their aggregation and precipitation (Cai and Tang, 2008;Mai et al, 2009;Zhong et al, 2015). PVPA, the other biomimetic analog, is a polyanion that imitates the negative charges of phosphoproteins (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…For mineral morphology based on fibrous extensions from PILP globules, osmotic pressure is a suggested factor. Here, a pressureinduced collapse of the outer (more dense) crust of the globules is suggested for the release of PILP precursors and crystallization as elongated structures (Olszta et al 2009). In an interesting perspective on rotational behavior of pearls, a high osmotic pressure at the mineral growth front, emerging from the exothermic mineralization processes and asymmetric mass transport, is suggested in the translation of microscopic forces into macroscopic dynamism (Cartwright et al 2013).…”
Section: Osmotic Conditions In Niche Spacesmentioning
confidence: 99%
“…As the roles of liquid-like precursors and coacervate phases of inorganic as well as organic systems are gradually being deciphered, their biological consequences emerge as significant in the field of mineralization. Stabilization of a transient inorganic liquid and amorphous phase by polymeric additives establishes a phase which exhibits liquid-like properties such as shape-adaptability (pseudomorphic transformation) and surface tension (Berg et al 2013;Bewernitz et al 2012;Gower and Odom 2000;Meldrum and Cölfen 2008;Olszta et al 2009). Such phases are suggested to play a fundamental role as a precursor phase in the morphogenesis of calcium-based biominerals such as enamel and bone (Olszta et al 2009).…”
Section: Mineralization and Liquid-like Phasesmentioning
confidence: 99%
See 1 more Smart Citation